2022
DOI: 10.1016/j.neubiorev.2021.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Neurocomputational mechanisms engaged in moral choices and moral learning

Abstract: The neural circuitry involved in moral decisions has been studied since the early days of cognitive neuroscience, mainly using moral dilemma. However, the neurocomputational mechanisms describing how the human brain makes moral decisions and learns in various moral contexts are only starting to be established. Here we review recent results from an emerging field using model-based fMRI, which describes moral choices at a mechanistic level. These findings unify the field of moral decision making, extend a concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 120 publications
(213 reference statements)
0
8
0
Order By: Relevance
“…A recent approach, mostly developed in adolescents and adults, has been to combine economic games (DG, UG, trust game), or new moral tasks (Rutledge et al 2016;van Baar et al 2019), with computational modelling and model-based fMRI to study the neurocomputational mechanisms underlying moral emotions. Using this approach, empathy, guilt and its anticipation, envy and other moral emotions, have been defined using computational models (Fehr & Schmidt 1999;Qu et al 2022).…”
Section: Moral Emotions In Adulthoodmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent approach, mostly developed in adolescents and adults, has been to combine economic games (DG, UG, trust game), or new moral tasks (Rutledge et al 2016;van Baar et al 2019), with computational modelling and model-based fMRI to study the neurocomputational mechanisms underlying moral emotions. Using this approach, empathy, guilt and its anticipation, envy and other moral emotions, have been defined using computational models (Fehr & Schmidt 1999;Qu et al 2022).…”
Section: Moral Emotions In Adulthoodmentioning
confidence: 99%
“…When making choices that weigh moral against monetary cost/benefit, areas of the brain involved in valuation are engaged (Qu et al 2022). In one study, a trade-off between moral cost and self-monetary benefit engaged the lateral PFC and the anterior insula (Qu et al 2019).…”
Section: Moral Learning and Decision Making About Others Moral Charac...mentioning
confidence: 99%
See 2 more Smart Citations
“…Functional neuroimaging studies have also consistently identified a set of interconnected regions underlying moral decision-making. This circuit includes the ventromedial prefrontal cortex (vmPFC), the ventral striatum (VS), the lPFC, and aINS (Qu et al, 2022;Yoder & Decety, 2018). Consistent with the common-currency hypothesis, some studies have demonstrated that the valuation system, including the vmPFC and VS, tracks the subjective value of voluntary donations and the appropriateness ratings of sociopolitical violence (Clithero et al, 2011;Hare et al, 2010;Workman et al, 2020).…”
Section: Introductionmentioning
confidence: 96%